1987
DOI: 10.1121/1.394915
|View full text |Cite
|
Sign up to set email alerts
|

Measures of phonation type in Hmong

Abstract: This study examines measures of glottal flow for vowels of Hmong, a Southeast Asian language which uses breathy and normal phonation contrastively. A software inverse filter was used to recover glottal airflow from oral airflow recordings. Properties of glottal flow measured in the time domain were glottal pulse symmetry and relative closed-phase duration. In the frequency domain, measures of spectral tilt and the amplitude difference between F0 and H2 were applied to discrete Fourier transforms (DFTs) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 8 publications
3
81
2
Order By: Relevance
“…It is not surprising that speakers would have a variety of phonatory strategies available to them for manipulating H1-H2 in speech. Listeners are highly sensitive to the relative amplitudes of the lowest harmonics (Kreiman et al, 2010b), which convey both paralinguistic information about a variety of personal and interpersonal attributes [see Kreiman and Sidtis (2011) for review] and linguistic information in languages like Gujarati (Fischer-Jorgensen, 1967), Chong (DiCanio, 2009), and White Hmong (Huffman, 1987). The ability to use different movements to produce the same speech sound has been described for the oral articulators (e.g., Guenther, 1994), and in the case of phonation may arise from attempts to produce a particular quality, whether for linguistic or paralinguistic reasons, in the context of different combinations of simultaneous pitch and/or loudness goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that speakers would have a variety of phonatory strategies available to them for manipulating H1-H2 in speech. Listeners are highly sensitive to the relative amplitudes of the lowest harmonics (Kreiman et al, 2010b), which convey both paralinguistic information about a variety of personal and interpersonal attributes [see Kreiman and Sidtis (2011) for review] and linguistic information in languages like Gujarati (Fischer-Jorgensen, 1967), Chong (DiCanio, 2009), and White Hmong (Huffman, 1987). The ability to use different movements to produce the same speech sound has been described for the oral articulators (e.g., Guenther, 1994), and in the case of phonation may arise from attempts to produce a particular quality, whether for linguistic or paralinguistic reasons, in the context of different combinations of simultaneous pitch and/or loudness goals.…”
Section: Discussionmentioning
confidence: 99%
“…[See Huffman (1987) and Sundberg et al (1999), for additional examples.] The same study also reported that while F0 is positively correlated overall with H1-H2, correlations for individual speakers are variable, with 18 cases positively correlated, 6 negatively correlated, and 4 with zero correlation (Swerts and Veldhuis, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Kreiman et al: Measures of the Glottal Source Spectrum the confusion surrounding voice quality terminology and without knowledge of the intercorrelations among acoustic measures, interpretation of such correlations is difficult. For example, Hammarberg, Fritzell, Gauffin, Sundberg, and Wedin (1980) reported correlations between various LTAS measures and breathiness, creakiness, and hypo/ hyperfunction; Klich (1982) found moderate correlations between rated breathiness and the relative spectral energy above 3500 Hz; and Huffman (1987) reported correlations between H1-H2 and phonemic breathiness in Hmong. In the face of such variability, drawing broad conclusions about the perceptual importance of various aspects of glottal source spectral slopes is difficult.…”
mentioning
confidence: 99%
“…For example, synthesis studies have shown that spectral features, including the difference in amplitude between the first and second harmonics (H1-H2), spectral tilt, and the bandwidth of the first formant, are associated with differences in voice quality (e.g., Bickley, 1982;Doval & d'Alessandro, 1999;Hanson, 1997;Klatt & Klatt, 1990). Some measures of the source spectrum (for example, H1-H2) also have well-established correspondences with linguistic features for voice quality (e.g., Huffman, 1987;Ladefoged, Maddieson, & Jackson, 1988;Wayland & Jongman, 2003).…”
mentioning
confidence: 99%
“…The low modal (-s) tone and the low-falling (checked) creaky (-m) tones are characterized by phonation, pitch, and duration differences. Production studies have shown that the phonation differences between these two tones are large (Esposito 2012, Garellek 2012, although for at least some speakers, the low-falling (-m) tone is sometimes realized simply as a short, checked tone with modal phonation (Huffman 1987, Ratliff 1992. There is an additional non-productive tone, the -d tone, which is a syntactic variant of the -m tone.…”
Section: Introductionmentioning
confidence: 99%